Safe ripening of fruits fetches more return - Bons, Harsimrat K; Mahajan, B V C (Indian Horticulture, 2019)
The ripening is a dramatic event in the life of fruit in which structural and compositional changes occur in unripe fruit to make it acceptable for eating purpose. It is generally irreversible in nature which marks the completion of development of fruit and commencement of senescence. However, the ability of a fruit to ripe is closely related to action of natural ripening hormone known as ethylene. The autocatalytic production of endogenous ethylene triggers ripening in climacteric fruits like banana, mango, pear, sapota etc. These fruits produce larger amount of ethylene during ripening and exposure to ethylene treatment results in quick and uniform ripening.